2014
DOI: 10.1016/j.bbamem.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Lipid modulation of ion channels through specific binding sites

Abstract: Ion channel conformational changes within the lipid membrane are a key requirement to control ion passage. Thus, it seems reasonable to assume that lipid composition should modulate ion channel function. There is increasing evidence that this implicates not just an indirect consequence of the lipid influence on the physical properties of the membrane, but also specific binding of selected lipids to certain protein domains. The result is that channel function and its consequences on excitability, contractility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 93 publications
0
62
0
Order By: Relevance
“…In this work, we demonstrated that this site can also accommodate LTB4. Therefore, two endogenous lipids from different chemical groups (heterocyclic cholane steroids and linear leukotrienes) can share their site of action on an ion channel protein, an unusual phenomenon because lipid-sensing sites on ion channels, BK in particular, do not share ligands from different lipid species (1,43). The physiological implications of such overlap remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we demonstrated that this site can also accommodate LTB4. Therefore, two endogenous lipids from different chemical groups (heterocyclic cholane steroids and linear leukotrienes) can share their site of action on an ion channel protein, an unusual phenomenon because lipid-sensing sites on ion channels, BK in particular, do not share ligands from different lipid species (1,43). The physiological implications of such overlap remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of ion channel function, of BK in particular, due to direct interaction between ion channel protein and physiologically relevant endogenous lipids represents a growing area of research (1,31). Indeed, several recent studies have shown direct modulation of BK channel function by fatty acids (10,32), phosphatidylinositol 4,5-bisphosphate and other phosphoinositides (8), membrane phosphoglycerides (33), and physiologically relevant steroids, including cholesterol (7,34), stress (35) and sex hormones (9), and bile acids and related cholane steroids (12,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, PAs have a strong affinity to calcium ion channels, PA binding to calcium ion channels can induce an outflow of intracellular Ca 2? [4]. We suppose that NSAIDs have certain effects on PAs when intervening in the inflammatory cell model.…”
Section: Introductionmentioning
confidence: 99%
“…PA substances can inhibit the release of intracellular Ca 2? , thereby reducing the endoplasmic reticulum stress caused by calcium and affecting macrophage endocytosis [4]. Moreover, PA substances can activate protein kinase C and other related pathways, thus affecting the cell cycle arrest and apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%